Cultural Diversity as a Competitive Advantage and The Importance of Cross-Cultural Management in the Internationalization Process of a company: The case of smart Europe GmbH - Pérez, Karen (My University, 2022)
Globalized economies, multinational corporations, rising migration flows, and a globally connected world have contributed to more intensive professional contact between people of various cultures. Hence, resulting in a more detailed display of intercultural differences and how these differences could affect individuals and their relationships with others in the workplace. Therefore, the main objectives of this research are to study the effect of this cultural diversity on the success of a company and the importance of managing the diversity through cross-cultural management during the internationalization process of a company. Consequently, answering the research questions “How can cultural diversity be a competitive advantage for a company? and Why is cross-cultural management important in the internationalization process of a company?” focusing on the case of smart Europe GmbH. The theoretical framework covers the relevant literature concerning cross-cultural management, multicultural teams, diversity as a competitive advantage, internationalization process, born global companies, global mindset, and the pan-European identity. Thus, these will be analyzed through a case study of the company smart Europe GmbH with a qualitative research method using semi-structured interviews with seven company employees. This thesis highlights the definition of a born-European company as a mixture of a born regional company and the international new venture definition, placed together with a pan-European business strategy and the characteristics this one possesses. It also shows the importance of a global mindset in the internationalization process of a company trying to expand and have a presence in different markets, together with the need for skilled employees who can understand and adapt to culturally different settings. Finally, the study underlines the importance of crosscultural management and the possible ways to allocate it since a company can have different settings depending on its level of multiculturalism and its identification as a company.
Keywords: internationalisation; corporate culture; cross-cultural research; diversity; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business